Association of Asymptomatic Diastolic Dysfunction Assessed by Left Atrial Strain With Incident Heart Failure - Potter, Elizabeth L.; Ramkumar, Satish; Kawakami, Hiroshi; Yang, Hong; Wright, Leah; Negishi, Tomoko; Marwick, Thomas H. (JACC. Cardiovascular imaging, 2020)
This study is to establish the association of left atrial reservoir strain (LARS) with incident heart failure (HF), and the impact of substituting LARS for left atrial (LA) volume index (LAVI) in diastolic assessment. LARS measures passive LA stretch and is a sensitive marker of left ventricular diastolic dysfunction (DD). The potential contribution of LARS to diastolic assessment is unclear. Baseline clinical and echocardiographic assessments were obtained in 758 asymptomatic, community-dwelling elderly subjects (age 70 [interquartile range: 67 to 74] years, 53% women) with nonischemic HF risk factors. LARS-defined DD (LARS-DD) was assessed by speckle-tracking echocardiography, and grades were assigned as normal (>35%), grade 1 (25% to 35%) and grade 2 (≤24%). DD grade using current recommendations was compared with grading using LARS <24% in place of LAVI >34 ml/m2. Patients were followed for up to 2 years for incident HF. LA strain analysis was feasible in 738 (97%) patients; average LARS was 39% (range 34% to 43%). Incident HF was associated with LARS-DD grade; 8 (36%) of those had grade 2+, 14 (10%) had grade 1, and 39 (9%) had normal function (p < 0.001). LARS-DD grade 2+ predicted incident HF after adjustment for clinical and echocardiographic markers (adjusted hazard ratio: 2.5; 95% confidence interval: 1.02 to 6.3; p = 0.049); there was no significant HF risk associated with LARS-DD grade 1. Dichotomized abnormal LARS <24% had an adjusted hazard ratio of 2.9 (95% confidence interval: 1.25 to 6.79; p = 0.013). Substituting LARS for LAVI provided a 75% reduction in indeterminate diastolic function; all were recategorized as normal. There was no increased risk associated normal diastolic function by this grading compared to conventional grading (C-statistic = 0.76 for both models). LARS-DD grade 2+ is associated with incident HF in the elderly, independent of LAVI. The substitution of LARS for LAVI reduces the number of indeterminate cases without impacting prognosis in normal diastolic function and grade 1 DD. [Display omitted]